Expression of Temporin G, an antimicrobial peptide from Rana temporaria using an Intein self-cleavage system in Escherichia coli - Kagri, Sabah Mushrafin (2021)
Temporins are a class of antimicrobial peptides (AMPs) naturally secreted from the skin of a common frog Rana temporaria especially under stressful condition. Temporin-G (TMPG) is a subclass of temporins with potent broad-spectrum antimicrobial activities. Although solid phase peptide synthesis (SPPS) is a common method used for the chemical synthesis of peptides, this method is technically demanding, involve the use of hazardous chemicals, and requires a well setup facility and the associated equipment for the overall operation which could be challenging for many laboratories. One of the promising alternatives for AMPs biosynthesis is by using the bacterial expression system. Expression of AMPs in Escherichia coli had been previously documented; however, the expressed AMPs would carry the vector-borne DNA sequences flanking the AMP-encoding gene. This gives rise to the undesired amino acid residues co-translated with the AMP which would alter the characteristics of the peptide expressed. Hence, we aim to construct an AMP recombinant expression system using the IMPACT-TWIN plasmid expression vector (intein mediated purification via affinity chitin-binding tag-two intein) for the biosynthesis of TMPG in its native form. The TMPG-encoding gene was cloned into pTWIN1 vector via N-terminal fusion to produce the pTWIN1-CBD-Int-TMPG vector. Transformants carrying pTWIN1-TMPG recombinant plasmid produced a band size of 277bp and DNA sequencing of the pTWIN1-TMPG amplicon further confirmed the orientation and sequence identity of the cloned TMPG encoding gene. Subsequently, the TMPG encoding gene was transformed into E. coli BL21 (DE3) cells and optimized for peptide expression by one-factor-at-a-time (OFAT) approach. That is, optimization of the various parameters influencing peptide expression in the host cell such as Isopropyl β- d-1-thiogalactopyranoside (IPTG) concentration, induction temperature, duration of induction, and the effect of agitation. Following the OFAT approach, the optimum condition for the induction of expression was determined to be using 0.9 mM IPTG at 25oC for 48h, coupled with shaking at 180rpm. The optimized induction produced a significantly higher protein expression which was 8-fold more than the pre-optimized conditions in the target pellet fraction and 7-fold more in the clarified cell lysate. Intein mediated purification system represents a promising bacterial recombinant expression system for the biosynthesis of native AMPs and a high peptide expression level was achieved following optimization for potential bioproduction of TMPG in the future.